A microRNA biogenesis-like pathway for producing phased small interfering RNA from a long non-coding RNA in rice. (18th February 2019) - Huang, Ji; Wang, Ruqin; Dai, Xinbin; Feng, Jiejie; Zhang, Hongsheng; Zhao, Patrick X
Abstract : Phased small interfering RNAs are produced in rice from a hairpin structure of a long non-coding RNA in a process that is independent of RNA-dependent RNA polymerases. Abstract: Phased small interfering RNAs (phasiRNAs) are a class of non-coding RNAs that perform essential functions in plants. Unlike microRNA biogenesis from a hairpin structure, the production of phasiRNAs usually requires a phase initiator and an RNA-dependent RNA polymerase (RDR) to form double-strand RNAs. By using full-length rice cDNA (KL-cDNA) to identify phasiRNA loci, we found that a putative non-coding sequence with a long hairpin structure generates the phasiRNAs, which we name Long Hairpin-structure containing non-coding RNA ( LHR ). The biogenesis of LHR -derived phasiRNAs was dependent on rice DCL4, but not on RDR2/6, DCL1, or DCL3. Since all of the LHR -phasiRNAs (-5p from the forward strand and -3p from the reverse strand of the dsRNAs) are mapped to the forward strand of LHR, LHR -phasiRNAs should be derived from its hairpin structure, similar to a microRNA precursor. A degradome-based validation suggested that several thylakoid-related genes were targeted by LHR -phasiRNAs. In addition, the production of LHR -phasiRNAs was completely abolished in the lhr mutant, which also exhibited decreased plant height, leaf size, and grain weight, probably through the regulation of photosynthesis. Based on our results, we propose a microRNA biogenesis-like pathway for producing phased siRNAs that expands our understanding of the current model of phased siRNA biogenesis in plants.